2008
DOI: 10.1291/hypres.31.931
|View full text |Cite
|
Sign up to set email alerts
|

Assiciations of Hypertension and Its Complications with Variations in the Xanthine Dehydrogenase Gene

Abstract: Hyperuricemia and oxidative stress participate in the pathophysiology of hypertension and its complications. Xanthine dehydrogenase (XDH) produces urate and, in its oxidase isoform, reactive oxygen species.Here we have studied whether or not the genetic variations in XDH could be implicated in hypertension and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…We were also interested in validating the transcriptional profiles of genes engaged in guanine, inosine and hypoxanthine degradation pathways, such as Gda (Guanine deaminase), Pnp (Purine nucleoside phosphorylase) and Xdh (Xanthine dehydrogenase) [32,33]. We found that all transcripts that are involved in these pathways were unaltered in the hearts of HD mouse models (Fig.…”
Section: Transcriptional Remodeling Of Genes Involved In the Synthesimentioning
confidence: 99%
“…We were also interested in validating the transcriptional profiles of genes engaged in guanine, inosine and hypoxanthine degradation pathways, such as Gda (Guanine deaminase), Pnp (Purine nucleoside phosphorylase) and Xdh (Xanthine dehydrogenase) [32,33]. We found that all transcripts that are involved in these pathways were unaltered in the hearts of HD mouse models (Fig.…”
Section: Transcriptional Remodeling Of Genes Involved In the Synthesimentioning
confidence: 99%
“…If true, this might also explain the lack of association, as a polymorphism that would increase serum levels would paradoxically reduce intracellular levels. Indeed, there is evidence that polymorphisms of XOR associated with increased activity are associated with hypertension [104,105].…”
Section: Limitations and Controversiesmentioning
confidence: 99%
“…However, these studies were either small or methodologically suboptimal to form the basis for treatment recommendations and the need of performing such a large trial in adults is perceived as a public health priority in the quest to prevent hypertension by intervening on this metabolic risk factor. Genetic variations in the enzyme that regulates the synthesis of uric acid have already been associated to hypertension, atherosclerosis and chronic kidney disease in a community study in Japan [18].…”
Section: Discussionmentioning
confidence: 99%